The surgeon - Gerritsen, Tess. (New York : Ballantine Books, 2001)
Dr. Catherine Cordell, recovering from a brutal attack and hiding her fear behind a mask of professionalism, is the only one that can stop a psychotic killer known as "The Surgeon," due to his horrific methods of murder, before he kills again.
Accelerated Reader AR
Maine author. Tess Gerritsen lives in Maine, with her family.
Keywords: Police -- Massachusetts -- Boston -- Fiction; Serial murders -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction